2016
DOI: 10.1136/bcr-2015-213704
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma: triple negative breast cancer with good prognosis

Abstract: Adenoid cystic carcinoma of the breast (ACCb) is a rare type of breast cancer. The treatment is not consensual. The authors report two cases of ACCb.Case 1: A 59-year-old woman with T1bN0M0, who went for lumpectomy and adjuvant radiation therapy (RT) (60 Gy in 30 fractions);Case 2: A 43-year-old woman, who went for modified radical mastectomy with T3N1M0, and underwent adjuvant chemotherapy, and a sequential regimen with antracyclin and taxane, prior to adjuvant RT (50 Gy/25 fractions).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…There have been no large scale studies to show benefit. Therefore, based on extrapolation of evidence in other breast cancer subtypes, chemotherapy has usually been reserved for patients who are young with large tumors or extensive nodal involvement . In our case series, distant disease occurred in the pleura and in one case the liver.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…There have been no large scale studies to show benefit. Therefore, based on extrapolation of evidence in other breast cancer subtypes, chemotherapy has usually been reserved for patients who are young with large tumors or extensive nodal involvement . In our case series, distant disease occurred in the pleura and in one case the liver.…”
Section: Discussionmentioning
confidence: 88%
“…Adenoid cystic carcinoma (ACC) or cylindroma is an extraordinarily rare subtype of breast cancer which accounts for fewer than 0.1% of all breast cancer diagnoses . It most frequently presents in post‐menopausal women with mean age of 50‐60 years.…”
Section: Introductionmentioning
confidence: 99%
“…[20] According to the percentage of the tumor that is solid, it can be divided into 3 grades. [21] Tumors with a higher percentage of solid mass always have more aggressive biological behavior. [12] The diagnosis of breast ACC in the frozen section is challenging because of histological complexity.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of axillary lymph node metastasis was less than 2% in previous reports. [21,22] Distant metastasis mostly occurred in the lung without lymph node infiltration. [20] Previous studies reported 5-year and 10-year overall survival rates of more than 95% and 90%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mean LRFS reported by case reports was 24 months (range 20-48) [3,4,8,[10][11][12]. Mean DFS reported by case series and retrospective series was 87.9% (range 69-100%) [2,5,[13][14][15][16]. Mean OS reported in case reports was 30 months (range 12-84) [3,4,8,[10][11][12].…”
Section: Resultsmentioning
confidence: 99%